Knowledge as a Driver of Regional Growth in the Russian Federation - Perret, Jens Kai.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The Russian Federation has a history of more than twenty years of transformation to a market economy, but as well to a knowledge society, to look back on. This study takes a look at the knowledge generation, knowledge transmission and knowledge use inside the Federation since the early 1990s. Furthermore, in light of the high dependence of the Russian economy on the oil and gas sectors this study analyzes the impact knowledge related factors have on regional income generation following thereby in the direction of Schumpeterian growth theory. The study combines descriptive with empirical analyses to paint a picture as detailed as possible of the Russian knowledge society and its innovative potential.
Introduction -- Regional Layout of the Russian Federation -- Relevant Economic Terms and Concepts in a Russian Context -- Growth Theoretical Aspects -- Methodology -- On the Importance of Knowledge in the Russian Federation -- Policy Option -- Conclusions.
Keywords: Economics; Geography; Endogenous growth (Economics).; Regional economics; Economics/Management Science; Economic Growth; Regional/Spatial Science; Economic Geography; R & D/Technology Policy; Educational Policy and Politics; Innovation/Technology Management